The association of park use and park perception with quality of life using structural equation modeling - Kodali, Hanish P.; Ferris, Emily B.; Wyka, Katarzyna; Evenson, Kelly R.; Dorn, Joan M.; Thorpe, Lorna E.; Huang, Terry T.-K. (Frontiers in Public Health, 2023)
The literature is limited on the impact of neighborhood parks on quality of life (QoL) and the mechanism linking them. In this paper, we applied the structural equation model to data from a cross-sectional sample of 650 participants in low-income communities of New York City, we examined the associations of neighborhood park use vs park perception and quality of life, and whether these associations were mediated through self-reported perceived stress. We also examined whether park use mediated the relationship between park perception and QoL. We found that park use had a significant but weak association with QoL (standardized β= 0.08, 95% CI: 0.02, 0.15, p =0.02), but this relationship was not mediated by self-reported stress. Park perception was more strongly associated with QoL than park use (standardized β= 0.23, 95%CI: 0.16, 0.30, p <0.01), and this was partly mediated by self-reported stress (Indirect effect- standardized β= 0.08, 95% CI: 0.03, 0.13, p <0.01) and, to a lesser extent, by park use (Indirect effect- standardized β=0.01, 95%CI: 0.00, 0.02, p=0.01). Having well-perceived parks appears to be an important factor for QoL independent of park use, suggesting that quality parks may benefit everyone in a community beyond park users. This strengthens the argument in favor of increasing park investment as a strategy to improve population wellbeing.